PENGEMBANGAN LKPD BERMUATAN STRATEGI “IDEAL” DALAM MATERI PROGRAM LINEAR TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS - Stepanus Daling; Edi Tandililing; Hamdani Hamdani (Universitas Tanjungpura, 2022)
AbstractThis research is a development research that refers to a 4D (four-D) development model that has been modified into 3D which includes three stages, namely: the definition stage, the design stage and the develop stage. The instrument used in this research is a questionnaire. The results of LKPD development are known that: (1) Based on the results of descriptive data analysis explaining that teachers and students need the development of LKPD containing the